Morphometry Of Maxillary Sinus and Its Clinical and Forensic Implications- A Ct Study - Singh, Monika; Ravi, Kumar Satish; Kapoor, Prince; Tiwari, Vineeta; khanduri, Sachin (Journal of Neonatal Surgery, 2025)
Introduction: Maxillary sinus is the largest paranasal air sinus located within the maxilla beneath the cheeks and above the upper teeth ,They are shaped like pyramids and drain into the middle meatus of the nasal cavity. These sinuses are crucial for lightening the skull and for conditioning the air with adding moisture and warmth. Material and Method: 355 individuals were taken for the study and were divided into four age groups 18-30 years, 31-40 years, 41-50 and 51-60 years. The measurements were recorded for right and left side maxillary sinus seperately.The cranio-caudal diameter, transverse diameter and anteroposterior diameter were measured statistical analysis was done. Results: The largest proportion of participants belonged to the 18 to 30 age group, accounting for 29.9% of the overall cohort. Subsequent age categories exhibited relatively uniform distributions, with 24.8%, 22.5%, and 22.8% in the 31 to 40 years, 41 to 50 years, and 51 to 60 years age ranges, respectively. There was a statistically significant association between the mean of height, width and depth of the right and left maxillary sinus. Conclusion: CT imaging offers critical insights into the size and shape of the maxillary sinuses across various age groups, making it an essential tool for age estimation. This information is highly valuable for clinicians, aiding them in surgical planning and decision-making